Finite element analysis of broken excavator boom welding cases and ascertaining its ability to restore its functions - ريحاوي, علاء (Latakia University Journal -Engineering Sciences Series, 2023)
The most important problems facing excavators during investment are the sudden breaks of their arms, which cause great material damage that leads to work stoppage, and the excavator breaks down as a whole. This research presents a detailed study of the performance of the arms used in the excavators after breaking and welding operations, taking into account the design of the arms in the excavators while they are exposed to compound static loads and dynamic loads similar to those that they can be exposed to in practice, as well as studying the effect of engineering parameters on the behavior of connections of a permissible type - Column with plate, the parameters studied are (plate thickness, additional joints and their number) separately. The research includes a detailed study of the behavior of welded joints at the place of breaking the arm and their parameters mentioned above using the finite element method, and knowledge of the different types of stresses and emerging transitions formed in each element of the arm in a way that allows a good understanding of the behavior of each element separately for each of the studied parameters, and thus arrive at The final result of the safety factor of the broken arm after welding and comparison of the results with the arm before cracking and breaking.